Using simulation to illuminate process improvement opportunities in a U.S. naval aircraft overhaul facility. Issue 14 (26th October 2017) - Heath, Susan; Yoho, Keenan D.
Abstract: Fleet Readiness Center Southwest (FRC SW) is the largest aerospace industrial complex in the U.S. Navy. The FRC SW conducts maintenance, repair and overhaul (MRO) activities on five major airframes with many of them being more than 20 years old. With demand for the aircraft in the field high, management at FRC SW were under enormous pressure to shorten the turn-around times of aircraft – the time between an aircraft being inducted for overhaul and the time it was returned to the warfighter for use in active military operations. Leadership at FRC SW requested the development of a simulation model that would incorporate all the important aspects of the complex and variable operating environment of their MRO facility and lend insight into how various factors and changes could affect the throughput time of aircraft across the facility. This research describes how the development and use of a simulation model uncovered several significant opportunities for management at FRC SW to increase turn-around time. The model also illuminated where simple policy changes could eliminate the need for additional capital investments, and where additional capital was needed the model indicated where it would yield the greatest return.